Hiperplasia linfoide cervical por difenilhidantoína. - Guillen, Daniel (2013)
We present the case of a three year old girl who showed two adverse reactions to DPH, one of them a large cervical lymphatic hyperplasia, which responded to discontinuation of the drug. Laboratory test were normal and histological examination showed non specific adenitis. We discuss this unusual case and the importance of the cervical adenopathy differential diagnosis.